Mechanisms and Therapeutic Roles of Medicinal Plants in Skin Photoaging - Lei X (Clinical, Cosmetic and Investigational Dermatology, 2025)
Xinxin Lei Department of Dermatology, Hangzhou Third People’s Hospital, Hangzhou Third Hospital Affiliated to Zhejiang Chinese Medical University, Hangzhou, 310009, People’s Republic of ChinaCorrespondence: Xinxin Lei, Department of Dermatology, Hangzhou Third People’s Hospital, Hangzhou Third Hospital Affiliated to Zhejiang Chinese Medical University, West Lake Road38, Hangzhou, 310009, People’s Republic of China, Tel +86-15273121767, Email leixinxin2025@163.comAbstract: Photoaging refers to the cumulative skin damage primarily caused by exposure to ultraviolet (UV) radiation. This process results in the harmful effects of UV irradiation on skin cells, leading to alterations in the extracellular matrix, which consequently impacts the appearance and function of the skin. This review aims to elucidate how bioactive compounds from medicinal plants counteract UV-induced damage, as identified by current mechanistic and molecular studies. Over the past few decades, medicinal plants have garnered increasing attention for their potential therapeutic benefits in treating various human diseases. Numerous studies have explored the anti-photoaging properties of herbal remedies, revealing that various active compounds, extracts, and combinations of medicinal plants can mitigate photoaging in different skin cells through diverse signaling pathways. Compared to synthetic agents, herbal remedies offer lower toxicity profiles and are often perceived as safer alternatives, making them attractive options for long-term skin care and photoaging prevention. These findings suggest that herbal plants can reduce UV-induced skin damage primarily by inhibiting the production of reactive oxygen species (ROS), matrix metalloproteinases (MMPs), and inflammatory mediators, while simultaneously promoting collagen synthesis. The underlying mechanisms of these effects are associated with key cellular pathways, including MAPK, NF-κB, Nrf2, and TGF-β/Smad. These findings suggest that herbal plants can reduce UV-induced skin damage by inhibiting reactive oxygen species (ROS), matrix metalloproteinases (MMPs), and inflammatory mediators, while promoting collagen synthesis. This review provides novel insight into cell-specific mechanisms by which medicinal plants mitigate photoaging, laying the groundwork for their potential therapeutic application.Keywords: photoaging, medicinal plants, herbs, matrix metalloproteinases, MMPs, reactive oxygen species, ROS, collagen